Review paper Acitretin, a systemic retinoid for the treatment of psoriasis – current state of knowledge - Pastuszka, Marta; Kaszuba, Andrzej (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Acitretin, a synthetic retinoid, is a pharmacologically active metabolite of etretinate. It replaced etretinate for the treatment of severe psoriasis (e.g. psoriatic erythrodermia and pustular psoriasis) because of its more favourable pharmacokinetic profile. Acitretin is 50 times less lipophilic than etretinate and has a shorter elimination half-life. However, there is evidence that small amounts of acitretin (especially in the presence of alcohol) are converted to etretinate. In psoriasis acitretin normalizes epidermal cell proliferation, differentiation and cornification. Acitretin appears to be as effective as etretinate (the effective dose of acitretin varies between 25 mg/day and 50 mg/day) and can be used in the same combination regimens. Teratogenicity is the most important safety issue (acitretin is FDA pregnancy category X). Other adverse effects are strongly related to the dose. It is unique compared to other systemic therapies for psoriasis (such as methotrexate and cyclosporine) in that acitretine is not an immunosuppressive agent.